SHOWCASING SOCIAL PIETY: BETWEEN CHARITY OF THE HAVES AND RIGHTS OF THE HAVE-NOTS - Miftahur Ridho (Islamic Communication Journal, 2018)
Religion based charity organizations, including those inspired by the Islamic teachings regarding caring for others, are prevalent around the world. They play significant role both in supporting the state to deliver social welfare services to the poor and the less fortunate and sidestepping or competing with the state in such provision. This paper, thus, aims at exploring the dynamic interplay between Islamic teachings regarding charitable practices and social welfare services provided by the state. Discussion on this paper suggests that Islamic charitable practices such as Zakat, shadakah, and others, can be observed through different lenses; as a charity of the rich and as rights of the poor. In Indonesia and other Muslim countries, such giving practices are widely accepted as charity of the rich partly because the idea of providing social welfare to the poor is perceived as the duty of the state. Hence, the rights of the poor lies on the obligation of the state, not the rich.Â